The Effect of Child Quantity and Education on Parents' Well-Being in Vietnam - Vu, Linh Hoang; Phung, Tung Duc (Frontiers in Public Health, 2021)
Vietnam currently has a rapidly aging population, while formal social protection has only covered a small fraction of older people. Therefore, many older people with insufficient income or poor health must rely on their children’s support. This study uses the Vietnam National Aging Survey 2011 to determine whether the quality of children’s education/employment and the number of children in a family impact older people’s life satisfaction and health. We find that the number of children has no effect on parents’ life satisfaction but is adversely related to parents’ health across a range of physical and mental health measures. In contrast, children’s education has beneficial impacts on the wellbeing of elderly parents. Specifically, parents with better-educated children are more satisfied with their lives and report better health and fewer illness issues. Among other factors, income and wealth are strong and consistent predictors of older people’s life satisfaction and self-perceived physical and mental health.